Comparative Kinetic Analysis of Butyrylcholinesterase Activity in Moroccan and Oasis Locusts (Gampsocleis Buergeri) - Ibragimova, Shakhodat; Burkhev, Farkhod; Kushiev, Khabib; Normatov, Anvar; Jumanov, Utkirjon; Asatov, Uralboy; Kamilova, Shakhlo; Rakhimov, Murodullo (International Journal of Aquatic Research and Environmental Studies, 2026)
Cholinesterases are essential neuroenzymes involved in synaptic signal transmission in insects and represent primary molecular targets of organophosphate and carbamate insecticides. However, comparative kinetic data on butyrylcholinesterase (BChE) activity among locust populations adapted to different ecological conditions remain limited. In the present study, BChE activity and kinetic parameters were comparatively investigated in Moroccan and Oasis locusts (Gampsocleis buergeri). Enzyme activity was determined spectrophotometrically using the Ellman method with butyrylthiocholine as substrate. Enzyme kinetics were analyzed by Lineweaver-Burk double reciprocal plots to calculate Michaelis-Menten constants. The results demonstrated pronounced interpopulation differences. Oasis locusts exhibited a lower Michaelis-Menten constant (Km = 6.71 × 10⁻⁵ M) and a higher maximum reaction velocity (Vmax = 4.037 × 10⁻⁶ mol·L⁻¹·min⁻¹) compared to Moroccan locusts (Km = 8.27 × 10⁻⁵ M; Vmax = 2.936 × 10⁻⁶ mol·L⁻¹·min⁻¹). These findings indicate higher substrate affinity and catalytic efficiency of BChE in Oasis locusts. Enhanced enzymatic performance suggests population-specific neuroenzymatic adaptation associated with environmental stress tolerance and differential sensitivity to neurotoxic compounds. The study provides new insights into insect neurophysiology and biochemical adaptation mechanisms relevant to pest management strategies.a
Keywords: butyrylcholinesterase; enzyme kinetics; Ellman method; locust neurophysiology; Gampsocleis buergeri; insect adaptation